A near infrared ratiometric platform based π-extended porphyrin metal-organic framework for O2 imaging and cancer therapy. (May 2021) - Xie, Bo-Ru; Yu, Yun; Liu, Xin-Hua; Zeng, Jin-Yue; Zou, Mei-Zhen; Li, Chu-Xin; Zeng, Xuan; Zhang, Xian-Zheng
Abstract: Photodynamic therapy (PDT) is widely researched in tumor treatment, but its therapeutic effect is affected by oxygen (O2 ) concentration of tumor site. Here, we developed a Pd-coordinated π-conjugated extended porphyrin doped porphyrin metal-organic-framework (named as PTP). PTP can achieve near infrared (NIR) O2 concentration ratiometric imaging, solving the problems of short detection wavelengths and influence of self-concentrations. With the NIR excitation wavelength and the ability of higher singlet oxygen ( 1 O2 ) generation, PTP can induce PDT more effectively. The efficient PDT also mediates cancer immunogenic cell death (ICD), which combines with the immune checkpoint inhibitor αPD-1 to achieve obviously cancer suppression and anti-metastasis effect. This theranostic NIR ratiometric nanoprobe can be used as a pre-evaluation on the outcome of PDT and high-efficient cancer combined treatment system, which will find great potential in tumor diagnosis and treatment. Graphical abstract: The theranostic near infrared ratiometric nanoprobe (PTP) could not only overcome the light penetration and influence of self-concentration in imaging O2 but also achieve good tumor treatment results by combination of photodynamic therapy and immunotherapy. Image 1